PRE-SERVICE MATHEMATHICS TEACHERS’ PREFERENCES IN USING MULTIPLE REPRESENTATION OF WORD PROBLEM SOLVING - Nurrahmawati, Nurrahmawati; Sa'dijah, Cholis; Sudirman, Sudirman; Muksar, Makbul (International Journal of Insights for Mathematics Teaching (IJOIMT), 2018)
Multiple representations have an essential role in the mathematics learning process for the students, pre-service and in-service teachers. It is important for them to understand the concept of mathematics and mathematical problem solving particularly in word problem-solving. However, pre-service teacher and in-service do not fully notice of using a variety of representations in the learning process. Thus, the purposes of this study are intended (1)  to find out the type of multiple representations used by pre-service teachers to solve the word problem by their own,  and (2) to figure out how they teach the process of word problem solving to the students. The participants of this research were the sixth-semester students of the Mathematics Education Program. Their written responses were analyzed and interviewed (semi-structured interview). The result showed that the types of multiple representations used by pre-service teachers are symbolic and verbal representations. Different multiple representations are used to help the student in word problem solving, even though pre-service teachers did not fully aware to apply them in their teaching activity. Hence, sharing the knowledge and the usage of multiple representations for pre-service mathematics teachers are urgently required in the real classroom setting.